SECOND LANGUAGE ACQUISITION AND ITS PSCYCHO-CULTURAL IMPLICATIONS - Dana Waskita (Fakultas Seni Rupa dan Desain ITB, 2009)
Bilingualism or multilingualism may imply socioeconomic advantages. But a further literature study indicates that this may also affect psychological and cultural viewpoints. The acquisition of second language would significantly influence the mentality or perceptual framework of the language users. Consequently, this finding may inspire to the appropriate pedagogical methods in language acquisition.